Pobreza, emoção e saúde: uma discussão sobre pentecostalismo e saúde no Brasil - Victor Vincent Valla (Revista Brasileira de Educação, 2002)
In the field of health and education, a debate has arisen about the causes of health problems. This debate maintains that the origin of health problems today is basically related to the emotions rather than viruses or bacteria. The theory of social support suggests that if the causes of health problems are basically emotional, then the solutions must also be related to the emotions. The so-called alternative therapies are proposed as a way of dealing with the emotions, together with the theory of social support. This theory holds that when people receive systematic emotional or material support from groups or institutions, this support is beneficial to their health. This raises the hypothesis that the cost of alternative therapies together with the difficulties encountered in the public health system in dealing with the sufferings of the poor help to explain the enormous growth of Pentecostal and evangelical churches among working-class populations in Brazil.